The copper beech - Binchy, Maeve (New York, NY : Delacorte Press, 1992)
Story of the youthful dreams of eight children, now adults leading different lives in the small Irish village of Shancarrig.
Kirkus Review.
Publisher's Weekly.
Wilson's Fiction.
Adult
Keywords: Country life -- Ireland -- Fiction; Villages -- Ireland -- Fiction; Ireland -- Fiction; Ireland -- Fiction; Pastoral fiction